Elevated Radiation Exposure Associated With Above Surface Flat Detector Mini C-Arm Use. (July 2019) - Martin, Dennis P.; Chapman, Talia; Williamson, Christopher; Tinsley, Brian; Ilyas, Asif M.; Wang, Mark L.
Background: This study aims to test the hypothesis that: (1) radiation exposure is increased with the intended use of Flat Surface Image Intensifier (FSII) units above the operative surface compared with the traditional below-table configuration; (2) this differential increases in a dose-dependent manner; and (3) radiation exposure varies with body part and proximity to the radiation source.Methods: A surgeon mannequin was seated at a radiolucent hand table, positioned for volar distal radius plating. Thermoluminescent dosimeters measured exposure to the eyes, thyroid, chest, hand, and groin, for 1- and 15-minute trials from a mini C-arm FSII unit positioned above and below the operating surface. Background radiation was measured by control dosimeters placed within the operating theater.Results: At 1-minute of exposure, hand and eye dosages were significantly greater with the flat detector positioned above the table. At 15-minutes of exposure, hand radiation dosage exceeded that of all other anatomic sites with the FSII in both positions. Hand exposure was increased in a dose-dependent manner with the flat detector in either position, whereas groin exposure saw a dose-dependent only with the flat detector beneath the operating table.Conclusions: These findings suggest that the surgeon's hands and eyes may incur greater radiation exposure compared with other body parts, during routine mini C-arm FSII utilization in its intended position above the operating table. The clinical impact of these findings remains unclear, and future long-term radiation safety investigation is warranted. Surgeons should take precautions to protect critical body parts, particularly when using FSII technology above the operating with prolonged exposure time.